PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS X MIPA SMAN 13 PADANG TAHUN PELAJARAN 2021/2022 - Arissa Septiana (Jurnal Edukasi dan Penelitian Matematika, 2022)
The purpose of this study was to analyze and describe the mathematical communication skills of students who were taught with the pair check type of cooperative learning model and the mathematical communication skills of students who were taught by the pair check type of cooperative learning model and the pair check type of cooperative learning. mathematical communication skills of students who are learning. This type of research is a quasi-experimental research (semi-experimental), with a Static Group Design research design. The population of this research is the students of class X MIPA SMAN 13 Padang who were registered in the 2021/2022. Based on hypothesis testing using t-test, obtained P-value < = 0.05, namely P-value = 0.000. That is, the mathematical communication skills of experimental class students who were taught by the pair check type cooperative learning model were better than the control class taught by conventional learning. Keywords–Pair Check, Conventional Learning, Mathematical Communication Skills